Molecular Detection of Tick-Borne Pathogens in American Bison (Bison bison) at El Uno Ecological Reserve, Janos, Chihuahua, Mexico - Beristain-Ruiz, Diana Marcela (2021)
American bison (Bison bison) is listed as near-threatened and in danger of extinction in Mexico. Recent studies have demonstrated the presence of several emerging pathogens at the Janos Biosphere Reserve (JBR), inhabited by one wild herd of American bison. Blood samples were collected from 26 American bison in the JBR. We tested for the presence of Anaplasma marginale, Babesia bigemina, B. bovis, Borrelia burgdorferi sensu lato, and Rickettsia rickettsii DNA using nested and semi-nested PCR protocols performing duplicates in two different laboratories. Results showed three animals (11.5%) positive for B. burgdorferi s. l., three more (11.5%) for Rickettsia rickettsii, and four (19.2%) for B. bovis. Two individuals were co-infected with B. burgdorferi s. l. and B. bovis. We found no animals positive for A. marginale and B. bigemina. This is the first report in America of R. rickettsii in American bison. American bison has been described as an important reservoir for pathogens of zoonotic and veterinary importance; thus, the presence of tick-borne pathogen DNA in the JBR American bison indicates the importance of continuous wildlife health surveys